SPIRIT OF MULTICULTURAL ISLAMIC RELIGIOUS EDUCATION IN BUILDING COMMUNITY TOLERANCE ATTITUDES - Zainuddin Zainuddin (Universitas Islam Malang, 2021)
The harmony and peace that appears in the majority Muslim community and vice versa is the majority of non-Muslims, it is very important to be investigated, especially in relation to cultivation and the form in maintaining it, among others with the attitude of Tasamuh. Therefore, the scope of this research is about the value of Tasamuh, how to internalize it, and the Tasamuh attitude model in increasing harmony for the community, which is based on Multicultural Islamic Religious Education in the villages of Kedungrejo.The purpose of this study was to describe, analyze, and provide interpretation of: The values of toleransi attitudes based on multicultural Islamic education in Kedungrejo Rowokangkung Lumajang and Tunjungrejo Yosowilangon Lumajang Villages. Internalization of the values of the Tasamuh attitude based on multicultural Islamic religious education in Kedungrejo Rowokangkung Lumajang and Tunjungrejo Yosowilangon Lumajang Villages. The community Tasamuh attitude model based on multicultural Islamic religious education in Kedungrejo Village Rowokangkung Lumajang.The research method used is qualitative with the type of multi case study research. Researchers collected data by means of in-depth interviews, participant observation, and documentation. Meanwhile, data analysis by presenting data, data reduction, and drawing conclusions in each case was then followed by a comparative study of the two cases. As for checking the validity of the researchers' data, it is done by means of credibility, transferability, dependability, and confirmability.This research resulted in: First, Tasamuh attitude values that continue to exist in the villages of Kedungrejo .The first case, such as the value of equality, the value of caring, the value of mutual respect, the value of positive exchange, the attitude of mutual help and recognition of everyone's rights. The second case is the value of patience, the value of grace, the value of loyalty to understanding others, the value of empathy and the value of togetherness. culture, Social Care, Social Service, Increased understanding, appreciation and experience of religious values.